2020
DOI: 10.1177/0954411920917557
|View full text |Cite
|
Sign up to set email alerts
|

The modified arterial reservoir: An update with consideration of asymptotic pressure (P) and zero-flow pressure (Pzf)

Abstract: This article describes the modified arterial reservoir in detail. The modified arterial reservoir makes explicit the wave nature of both reservoir ( Pres) and excess pressure ( Pxs). The mathematical derivation and methods for estimating Pres in the absence of flow velocity data are described. There is also discussion of zero-flow pressure ( Pzf), the pressure at which flow through the circulation ceases; its relationship to asymptotic pressure ( P∞) estimated by the reservoir model; and the physiological inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 111 publications
(161 reference statements)
1
19
0
Order By: Relevance
“…Details of the reservoir approach are provided elsewhere (Hughes and Parker, 2020). In brief, it is assumed that reservoir pressure, P res , satisfies overall conservation of mass for the circulation: where Q in is the volumetric flow rate into the aortic root, C is the net compliance of the arteries, k d is the diastolic rate constant (the reciprocal of the diastolic time constant τ = RC , where R is the resistance to outflow through the microcirculation, and P zf is the pressure at which outflow through the microcirculation ceases.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the reservoir approach are provided elsewhere (Hughes and Parker, 2020). In brief, it is assumed that reservoir pressure, P res , satisfies overall conservation of mass for the circulation: where Q in is the volumetric flow rate into the aortic root, C is the net compliance of the arteries, k d is the diastolic rate constant (the reciprocal of the diastolic time constant τ = RC , where R is the resistance to outflow through the microcirculation, and P zf is the pressure at which outflow through the microcirculation ceases.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, although AIx increases with age, it plateaus and may even decrease around middle age ( Kelly et al, 1989 ; Mitchell et al, 2004 ; Fantin et al, 2006 ); it has been argued that this plateau does not necessarily mean that wave reflection is decreasing, but is a result of mathematical division between two linearly increasing curves (AP and PP) ( Namasivayam et al, 2010 ). Davies et al (2010) concluded that systolic augmentation was mainly related to reservoir pressure, with only a minor contribution from reflected waves; however, this interpretation now appears moot because current (revised) views acknowledge that wave reflection produces the reservoir pressure ( Hughes and Parker, 2020 ). Nevertheless, AIx has also been shown to depend on ventricular outflow patterns ( Karamanoglu and Feneley, 1999 ), preload ( van de Velde et al, 2017 ), contractility/relaxation properties ( Cheng et al, 2012 ) and forward waves ( Fok et al, 2014 ), although these dependencies may relate in part to re-reflection of backward-traveling waves when they return to the ventricle ( Phan et al, 2016a ).…”
Section: Pulse Wave Analysismentioning
confidence: 99%
“…The latter signifies the pressure that would exist if no pressure differentials existed throughout the circulation, and may therefore be identified with mean circulatory pressure ( P mc ) ( Mynard and Smolich, 2014b ). Alternatively, P ud could be identified with the zero-flow or asymptotic pressure that is reached after a long period of asystole, which may not be equal to P mc ( Hughes and Parker, 2020 ).…”
Section: Wave Potentialmentioning
confidence: 99%
See 2 more Smart Citations